Інститут кураторства як складова виховних технологій при формуванні особистості студента у закладах вищої освіти - Коваленко, Олександр Іванович; Kovalenko, O. (Запоріжжя : ТДАТУ, 2024)
UA: Робота присвячена аналізу впливу інституту кураторства на формування особистості здобувача вищої освіти при впровадженні та використанні виховних технологій у закладах вищої освіти (ЗВО). EN: The work is devoted to the analysis of the influence of the institution of curatorship for the formation of the personality of the student of higher education during the implementation and use of educational technologies in institutions of higher education.
The institute of curatorship as a component of educational technologies in the formation of student personality in institutions of higher education
Keywords: куратор; інститут кураторства; виховні технології; здобувач вищої освіти; колективне творче виховання; особистість; curator; institute of curatorship; educational technologies; student of higher education; collective creative education; personality